Influence of Fertilization System on Wheat Yields in Terms of Global Climate Change - Miroslav Jelić; Olivera Nikolić; D. Knezevic; Nadica Savic; G. Dugalić (Journal of Economic Development, Environment and People, 2013)
Over the last few decades, wheat production, both in Serbia and worldwide, has been practiced under characteristic agrometeorological conditions. It has generally been affected by specific strongly marked agrometeorological and climate extremes, most notably extreme temperature and drought events during critical periods in the growing season, which mostly had a negative impact on the growth, development and yield of wheat in Central Serbia.